Best Practices for Implementing the Case Method and Team-Based Project Models: Efforts to Fulfill Higher Education Key Performance Indicators - Puspita, Entit; Sispiyati, Ririn; Agustina, Fitriani (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
This study describes the best practices of implementing case methods and team-based projects in Consulting Project lectures related to achieving Higher Education Key Performance Indicators (KPI-HE). The study used a qualitative descriptive method to describe and depict the best practices of implementing case method and team-based project models in Consulting Project lectures. The research participants were 82 students taking consulting project lectures in the Mathematics Study Program. The case method and team-based project models were carried out simultaneously in lectures, directly confronting students with real problems, challenging students to develop creativity and critical thinking in determining various alternative solutions. The creation of various alternative solutions to partner issues and the formal signing of the Cooperation Agreement between the study program and partners prove that the consulting project lecture supports the achievement of the study program's KPI, especially KPI 6 related to partnerships and KPI 7 related to collaborative participatory classes. The best practices reported in this study will contribute to the study program in improving the quality of learning and, in general, in revising the curriculum, especially for courses aimed at training students to become part of the world of work and industry.